Improved performance of near infrared excitation Raman spectroscopy using reflective thin-film gold on glass substrates for cytology samples - O'Neill, Luke (My University, 2019)
Confocal near-infrared Raman spectroscopy has been shown to have applications in the area of clinical biology. A source wavelength in the near infrared is preferred over visible wavelengths for inspecting biological samples due to superior wavenumber resolution and reduced photodamage. However, these excitation sources have a number of drawbacks when compared to lasers in the visible wavelength region, including the requirement to use expensive highly pure crystal substrates such as Raman grade calcium fluoride as well as long acquisition times due to the lower Raman scattering efficiency. This paper investigates the use of a reflective substrate comprising a low cost 100 nm thin-film gold on glass substrate, as an alternative. Similar to recent work that used stainless steel substrates, it is demonstrated that the thin-film gold coated substrates, which are relatively inexpensive, produce cell spectra with 1.65 times the signal to noise ratio when compared with spectra obtained from calcium fluoride under identical conditions, with no apparent background signal in the fingerprint region. Two prostate cell lines are examined having been deposited on glass, calcium fluoride, and thin-film gold on glass substrates using the ThinPrep standard. Background spectra from, and cell adhesion on, these three substrates are compared. A comparison of the intensities and signal to noise ratios of the resulting spectra, and their viability for classification using principle components analysis is performed, which further demonstrates the benefit of reflective substrates.
Keywords: calcium fluoride; Confocal near-infrared Raman spectroscopy; reduced photodamage